Recent advances in the treatment of chronic heart failure - Buckley, Leo F (F1000Res, 2019)
After more than a decade of relatively modest advancements, heart failure therapeutic development has accelerated, with the PARADIGM-HF trial and the SHIFT trial demonstrated significant reductions in cardiovascular death and heart failure hospitalization for sacubitril-valsartan and in heart failure hospitalization alone for ivabradine. Several heart failure therapies have since received or stand on the verge of market approval and promise substantive advances in the treatment of chronic heart failure. Some of these improve clinical outcomes, whereas others improve functional or patient-reported outcomes. In light of these rapid advances in the care of adults living with chronic heart failure, in this review we seek to update the general practitioner on novel heart failure therapies. Specifically, we will review recent data on the implementation of sacubitril-valsartan, treatment of functional mitral regurgitation, sodium-glucose co-transporter-2 (SGLT-2) inhibitor therapy, agents for transthyretin amyloid cardiomyopathy, treatment of iron deficiency in heart failure, and the use of biomarkers or remote hemodynamic monitoring to guide heart failure therapy.